Maximizing flux pinning in YBCO coated conductor films for high-field applications - Vaimala, Tuomas; Aye, Moe Moe; Rivasto, Elmeri; Zhao, Yue; Huhtinen, Hannu; Paturi, Petriina (Elsevier, 2025)
Our study explores the relationship between BZO nanorod density and magnetic flux pinning in YBCO thin films on coated conductor templates. We identified an optimal BZO doping level of 8%–10%, which maximizes flux pinning and enables the highest critical current densities to be achieved across various temperatures and magnetic field ranges, especially in new types of multilayer structures. Additionally, the formation of a c-axis peak in the angular-dependent critical current curves at high BZO concentrations underscores the significance of collective pinning mechanisms. These results are discussed using a simple pinning model that considers the effects of nanorod spacing and fragmentation. Overall, our findings contribute to the development of high-performance coated conductor layer structures for future power applications, where maximizing flux pinning is essential.